Factors Livestock And Milking Associated With Risk Of Mastitis In Cattle Dairy Farms In Aboveground Of The Tunisia Coastal Semi-arid - M’sadak, Y.; Mighri, L.; Haj Mbarek, R.; Kraiem, K. (University of Eloued جامعة الوادي, 2013)
This study was carried out in the Sahel of Tunisia (Monastir region) on a sample covering 40 cattle herd’s type above ground. We deduced the mastitis risk factors during the survey during visits for breeding and milking as well as from morphological and hygienic cow’s assessments. The data’s descriptive analysis has highlighted some significant effect factors on cellular levels and the risk of developing mastitis. For individual cell count (ICC), the significant effect factors (P <0.05) are: free stall, milking machine cleaning with only water, the poor condition of the piping, not elimination of the first milk jets and bad cleanliness of udders and the back legs of cows, whereas the herd cell count (HCC), the significant factors (P <0.05) are: cleaning the milking machine with water only, the frequency pulse (FP) is too high or low.
Articale in Journal of fundamental and Applied Sciences Vol. 05 N. 02
Keywords: Dairy cows, Breeding and milking conditions; Somatic cell counts, Breast infections, Risk factors.